1-dimensional unsteady non-uniform dynamic flood modelling of San Juan River and its tributaries using HEC-RAS - Estardo, Allexby C.
San Juan River, the main waterway in Quezon City, had been identified by the Department of Public Works and Highways (DPWH) as one of the priority rivers part of the Php351-billion worth of flood control master plan for Metro Manila to be implemented until 2030. [18] Even since 1999 during Pres. Estrada's administration, it had been a subject of multiple flood mitigation measures such as channel dredging and construction of floodwall. [14] However, until now the issue of flooding due to river overflow even under prolonged rainfall only and not of actual typhoon-induced flood per se, has been perpetuating. This is primarily attributed to shallowing of the main channel due to heavy siltation and garbage accumulation. Aside from that, informal settlers encroaching along the banks narrowed down the channel width of the river. In this research, a numerical hydraulic model was developed to replicate the actual conditions of San Juan River and its response during a flooding event to better understand its hydraulic behavior. A 1-dimensional unsteady, gradually-varied flow regime was employed in the HEC-RAS software. Discharge data from hydrologic modelling of two storm events were used as upstream flow boundary condition while water level time series from Pandacan Station were considered as downstream boundary condition at the confluence with Pasig. The model was calibrated in relation to Habagat of 2012 while Typhoon Mario of 2014 was used to validate the model results. Water level measurements from Sevilla Bridge Station were used as basis for comparison of results since it has the most complete data among all the stream gauges installed along San Juan River. An RMSE of 0.1816m was obtained after the final calibration of the model. This translates to an error of 6.435% with respect to the hydraulic mean depth of the cross section RS 1586.999 located at Sevilla Bridge. Meanwhile, an RMSE of 0.35m was obtained after validating the model - an error of 12.41% in relation to the hydraulic mean depth. The increase in error was attributed to the fact that the model seem to overestimate stage heights during peak flows because only the channel is being considered in the model. Overall, the model performs within acceptable limits of accuracy when modelling storm events yielding not too large of discharge.